The anti-corruption mindset of Brazilian law enforcers - Trombini, Maria Eugenia; Valarini, Elizângela (Organizational crime, 2023)
Recent studies on the fight against corruption in Brazil focus on institutional improvements, mainly through the interaction between the units that are part of a more general accountability network, seen as enablers of high-profile investigations such as Operation Car Wash. There is much discussion on the role of legislation, means of control, investigation and processing of crimes, changes in the design of state agencies; however, little is known about the cognitive and normative processes of the agents working in anti-corruption within the justice system. Our central question in this chapter is to understand the “fight against corruption” in Brazil from the standpoint of legal professionals. Using the qualitative method of collective mindset analysis, we will reconstruct the interpretative and normative standards of the actors of the justice system when faced with the problem of how to counter corruption in Brazil. Mapping the stocks of knowledge accessed by the investigated group, we wish to trace the meaning they attribute to their actions to justify and explain the “solutions” chosen to deal with the phenomenon. We discuss the results based on a sample of 12 qualitative interviews with judges, prosecutors, and defense attorneys involved in major corruption cases in recent decades, and find that specialized knowledge, often acquired when “learning abroad”, is an important aspect of the reconstructed collective interpretation patterns.